Dementia inclusivity: Using the experiences of people with dementia and care partners to inform a forum intended to address community attitudes - Read, Sheridan Tracy (Curtin University, 2022)
The number of people diagnosed with dementia is increasing globally and there is a necessity to find measures to support their quality of life. This mixed methods research study explored the experiences and expectations of people diagnosed with dementia and their care partners to determine their current and future needs. It included the implementation and evaluation of a Dementia Awareness Raising Forum to bring about more positive community attitudes towards this cohort of people.